The historians of the centennial generation: their youthful letters - Castro de Trelles, Lucila (2021)
The article presents the historical context and fragments, as well as unpublished letters of Jorge Guillermo Leguía, Emilia Romero, Jorge Basadre and Raúl Porras Barrenechea, which show in part how and what those young historians of the socalled centennial generation thought.